Advances in Knee Surgery - In, Yong; Koh, In Jun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the orthopedic surgical field, knee surgeries, including articular cartilage repair procedures, meniscus surgery, ligament reconstruction surgery, osteotomy surgery, and partial/total knee arthroplasty surgery, have made great advances over the last few decades. This Special Issue highlights and focuses on the surgical concepts and techniques, decision-making processes, perioperative management protocols, and clinical outcomes of the recent various advanced knee surgery procedures.